Environmental & architectural phenomenology. Vol. 27, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2016)
Vol. 27, No. 1, Winter 2016 (includes “items of interest,” “citations received,” book review of Christopher Tilley’s Interpreting Landscapes, and essays by Dylan Trigg, Stephen Wood, Jenny Quillien, Victoria King, and Gary J. Coates)
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals